2020
DOI: 10.12669/pjms.36.7.2544
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical application values of PCT, hs-CRP and SAA detection in the early diagnosis of sepsis

Abstract: Objectives: To investigate the clinical application values of procalcitonin (PCT), high-sensitivity C-reactive protein (hs-CRP) and serum amyloid A (SAA) in the early diagnosis of sepsis. Methods: In this retrospective analysis, 36 patients admitted to Liaocheng People’s Hospital were selected from May 2018 to July 2019. According to infectious disease diagnostic criteria, 17 patients were confirmed to have sepsis (observation group), and 19 patients were determined to be nonseptic (control group). The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Early analysis and prediction of a patient's disease may provide a plan for early diagnosis as well as treatment and prevention. 10,11 The results of this study showed that the levels of SII, IL-35 and HMGB-1 in Group-A were significantly lower than those in Group-B, and those in the survival group were all lower than those in Group-B. Further correlation analysis showed that the three indexes of SII, IL-35 and HMGB-1 were significantly positively correlated with the disease severity and prognosis of patients with sepsis, suggesting that patients with sepsis showed an increased inflammatory response and decreased immune function, and the inflammatory status and immune level were unbalanced with the development of the disease.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…Early analysis and prediction of a patient's disease may provide a plan for early diagnosis as well as treatment and prevention. 10,11 The results of this study showed that the levels of SII, IL-35 and HMGB-1 in Group-A were significantly lower than those in Group-B, and those in the survival group were all lower than those in Group-B. Further correlation analysis showed that the three indexes of SII, IL-35 and HMGB-1 were significantly positively correlated with the disease severity and prognosis of patients with sepsis, suggesting that patients with sepsis showed an increased inflammatory response and decreased immune function, and the inflammatory status and immune level were unbalanced with the development of the disease.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…Currently, blood cultures are the gold standard for the diagnosis of bloodstream infections, but they are time-consuming, taking 3–7 days or more, with poor timeliness and the possibility of contaminated specimens ( 9 ). In recent years, some clinical studies have found that the levels of inflammatory factors such as calcitoninogen (PCT) and C-reactive protein (CRP) have high clinical value in the early diagnosis of sepsis and determination of the disease ( 10 , 11 ). PCT and CRP are two important inflammatory cytokines that are involved in apoptosis and can enable cell lysis, and their levels are significantly increased when the organism is infected with bacteria, but the relevance of changes in their levels has been less studied in patients with sepsis due to bloodstream infection ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 70.5% of the included patients had lower respiratory infection, and the septic population may affect the result. Additionally, PCT is often used as a biomarker to distinguish the presence of bacterial infection [ 23 ]. However, in the present study, we included septic patients with different kinds of pathogens, which might influence the results.…”
Section: Discussionmentioning
confidence: 99%